β-crystals aied greater energy absorbing ethylene–propylene rubber in polypropylene blends for outstanding low-temperature toughness - Ruimiao Liang; Wenwen Yu; Jiahao Shen; Zhiyi Zhang; Zaifu Lin; Jiayi Wang; Lan Jia; Feng Chen; Yonggang Shangguan; Qiang Zheng (Polymer Testing)
Modulating the β-crystalline phase and adding elastomers have traditionally been used to overcome the brittleness of polypropylene (PP); however, the synergistic mechanisms of these components in enhancing low temperatures toughness remain insufficiently explored. A β-nucleating agent (TMB-5) was incorporated into the polypropylene/ethylene–propylene rubber (PP/EPR) system to address the challenges of enhancing low-temperature toughness. Under an extreme low-temperature condition of −40 °C, the PP/EPR/TMB-5 blends exhibit a remarkable enhancement in low-temperature toughness compared with PP/EPR blends, showing a 138 % increase to reach 38.3 kJ/m2. In addition, these blends demonstrate an 8.47 % increase in tensile strength at room temperature. The addition of TMB-5 provides numerous nucleation sites that facilitate the β-crystallization of polypropylene, leading to an increased content of β-crystals and a reduction in crystal grain size. Broadband dielectric relaxation spectroscopy shows that the constrained relaxation of EPR near the crystals shifts to higher temperatures with the formation of β-crystals. The lamellar structure of the β-crystals prevents the aggregation of EPR rubber domains during cooling process, resulting in reduced rubber particle spacing. Observations of remarkable shear deformation and extensive stress-whitening areas on the fracture surfaces of PP/EPR/TMB-5 blends upon impact at −40 °C, as opposed to PP/EPR blends, underpin that the lamellar structure of β-crystals within the composite material efficiently transmits stress further away, facilitating the involvement of more EPR particles in energy dissipation. This finding enables an in-depth investigation into the synergistic toughening mechanism and provides new insights into blends design with conventional rubber for extreme conditions.